2023
DOI: 10.3748/wjg.v29.i28.4416
|View full text |Cite
|
Sign up to set email alerts
|

γ-aminobutyric acid B2 receptor: A potential therapeutic target for cholangiocarcinoma in patients with diabetes mellitus

Abstract: The human intestine is a natural environment ecosystem of a complex of diversified and dynamic microorganisms, determined through a process of competition and natural selection during life. Those intestinal microorganisms called microbiota and are involved in a variety of mechanisms of the organism, they interact with the host and therefore are in contact with the organs of the various systems. However, they play a crucial role in maintaining host homeostasis, also influencing its behaviour. Thus, microorganis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…The underlying mechanisms are known to involve the effects of hyperglycemia and probably the effects of hormonal disturbances 16 , 17 , 30 , 31 . Our previous reports demonstrated that high glucose level is a promoting factor for CCA via the activating effects on multiple signaling pathways 16 18 . However, where the effects of exogenous insulin on CCA development and progression remain controversial 31 , some anti-diabetic medications, e.g., metformin, show potential effects on the reduction of risk of CCA development and tumor aggressiveness 32 , 33 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The underlying mechanisms are known to involve the effects of hyperglycemia and probably the effects of hormonal disturbances 16 , 17 , 30 , 31 . Our previous reports demonstrated that high glucose level is a promoting factor for CCA via the activating effects on multiple signaling pathways 16 18 . However, where the effects of exogenous insulin on CCA development and progression remain controversial 31 , some anti-diabetic medications, e.g., metformin, show potential effects on the reduction of risk of CCA development and tumor aggressiveness 32 , 33 .…”
Section: Discussionmentioning
confidence: 99%
“…Diabetic hyperglycemia can induce growth and metastatic activities of CCA cells in vitro via multiple pathways, i.e., signal transducer and activator of transcription 3 (STAT3) 16 , nuclear factor-kappa B (NF-κB) 17 , and glycogen synthase kinase 3/β-catenin pathways 18 . In addition, metformin, the first-line therapy for DM type 2, exerts anti-proliferative and anti-metastatic activities against CCA cells by targeting STAT3 and NF-κB 19 and enhancing chemotherapeutic sensitivity of CCA to cisplatin, the standard chemotherapy 20 .…”
Section: Introductionmentioning
confidence: 99%
“…By contrast, little is known about the role of GABBR2 in neoplastic conditions. Limited and somehow conflicting data have demonstrated that GABA B receptor agonists either promote (e.g., breast [ 34 ], kidney [ 35 ], and prostate [ 36 ] cancers) or inhibit (e.g., lung cancer [ 37 ], cholangiocarcinoma [ 38 , 39 ]) the cell growth of nonurothelial malignancies. Particularly, in the prostate cancer study [ 36 ], an AR-negative cell line was tested, although the role of AR signaling in its progression and treatment has been extremely well established.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, the elevated expression of GABBR2 has been reported in several types of neoplasm such as thyroid adenoma and carcinoma [ 47 ] and non-small cell lung cancer [ 37 ]. In cholangiocarcinoma specimens, high GABBR2 expression was strongly associated with more aggressive nonpapillary histology yet small tumor size [ 39 ]. By analyzing a public database (i.e., The Cancer Genome Atlas (TCGA)), GABBR2 overexpression was linked to lower T and N staging categories and better prognosis in patients with breast cancer [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Other medications that increase insulin secretion or its bioavailability, e.g., sulfonylurea and insulin analogs, neither show the effects on CCA development and progression ( 17 ). On the other hand, hyperglycemia and other medications are suggested for their involvement in CCA progression or recession ( 18 , 19 ). Later studies are, therefore, mainly focused on the impacts of high glucose levels and anti-diabetic medications on the modifications of risk and progression of CCA.…”
Section: Introductionmentioning
confidence: 99%